2006
DOI: 10.1038/ng1898
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of Jun family transcription factors in PU.1 knockdown–induced leukemic stem cells

Abstract: Knockdown of the transcription factor PU.1 (encoded by Sfpi1) leads to acute myeloid leukemia (AML) in mice. We examined the transcriptome of preleukemic hematopoietic stem cells (HSCs) in which PU.1 was knocked down (referred to as 'PU.1-knockdown HSCs') to identify transcriptional changes preceding malignant transformation. Transcription factors c-Jun and JunB were among the top-downregulated targets. Restoration of c-Jun expression in preleukemic cells rescued the PU.1 knockdown-initiated myelomonocytic dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
151
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(167 citation statements)
references
References 49 publications
13
151
0
3
Order By: Relevance
“…1,2,8,9,20,41 It has been shown that leukemia-initiating cells can reside in different phenotypic stem and progenitor compartments at relatively low frequencies and are associated with transcription factor alterations that result in pathogenic transcriptional changes. [2][3][4][5][6][7][11][12][13]32,[42][43][44] Thus, to uncover newer stem cell-directed targets, we conducted a transcriptomic analysis on rigorously defined stem and progenitor populations in AML and MDS in comparison with their respective healthy counterparts. With this approach, we were able to identify IL8 as one of the few genes most significantly overexpressed across different stem and progenitor subsets in AML and MDS patients, indicating it might play a crucial role in the pathogenesis of AML and MDS.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,8,9,20,41 It has been shown that leukemia-initiating cells can reside in different phenotypic stem and progenitor compartments at relatively low frequencies and are associated with transcription factor alterations that result in pathogenic transcriptional changes. [2][3][4][5][6][7][11][12][13]32,[42][43][44] Thus, to uncover newer stem cell-directed targets, we conducted a transcriptomic analysis on rigorously defined stem and progenitor populations in AML and MDS in comparison with their respective healthy counterparts. With this approach, we were able to identify IL8 as one of the few genes most significantly overexpressed across different stem and progenitor subsets in AML and MDS patients, indicating it might play a crucial role in the pathogenesis of AML and MDS.…”
Section: Discussionmentioning
confidence: 99%
“…The C/EBPa LZ also competes with c-Jun for interaction with PU.1 in the absence of DNA (Reddy et al, 2002), but when bound to DNA C/EBPa may in specific contexts, like C/EBPb, augment PU.1 activity as these factors cooperatively activate myeloid promoters (Oelgeschla¨ger et al, 1996). c-Jun rescues monocytic differentiation in PU.1-knockdown marrow cells (Steidl et al, 2006), but its effect in PU.1(À/À) cells has not been evaluated. Also of note, c-Jun and JunB levels are reduced in PU.1-knockdown HSCs, although PU.1 binds the JunB but not the c-Jun promoter (Steidl et al, 2006).…”
Section: Pu1mentioning
confidence: 99%
“…c-Jun rescues monocytic differentiation in PU.1-knockdown marrow cells (Steidl et al, 2006), but its effect in PU.1(À/À) cells has not been evaluated. Also of note, c-Jun and JunB levels are reduced in PU.1-knockdown HSCs, although PU.1 binds the JunB but not the c-Jun promoter (Steidl et al, 2006). c-Jun or c-Fos interacts with and prevents C/EBP bZIP DNA-binding, even if the c-Fos or c-Jun BRs are deleted, suggesting direct interaction via their LZ domains (Hsu et al, 1994).…”
Section: Pu1mentioning
confidence: 99%
“…In contrast, other transcription factors, (for example, PU.1 and JunB) may display reduced expression in AML stem cells. 178,179 Targeting of transcription factors has proven problematic, however, it is an area which has great potential. 180 In summary specific therapeutic targeting of the leukemic stem cells is a field in its infancy.…”
Section: Targeting the Leukemic Stem Cellmentioning
confidence: 99%